Pengaruh Price, Online Customer Rating, dan Online Customer Review terhadap Keputusan Pembelian di Marketplace Shopee - Linda Dian Utami; Christiawan Hendratmoko (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
This study aims to determine the effect of price, online customer rating, and online customer review on purchasing decisions partially. The study used a quantitative approach, involving 150 respondents who shopped for fashion products through the Shopee application. Data analysis in this study used multiple linear analysis. Based on the research conducted, the results obtained that price (X1) has a significant effect on purchasing decisions, online customer rating (X2) does not have a significant effect on purchasing decisions, online customer review (X3) has a significant effect on purchasing decisions. The magnitude of the influence of price, online customer rating, and online customer review on purchasing decisions is 48.2%, while the remaining 51.8% is influenced by other variables not listed in this study.